Magnetic Properties of Electrodeposited Cobalt-Platinum (CoPt) and Cobalt-Platinum-Phosphide (CoPtP) Thin Films - Park, D.-Y.; Myung, N. V. (Frontiers in Chemistry, 2021)
CoPt and CoPtP thin films were synthesized using direct current (DC) aqueous electrodeposition from weak alkaline solutions. The basic plating solutions of binary CoPt thin films consisted of cobalt pyrophosphate [Co2P2O7] and chloroplatinic acid [H2PtCl6]. Various amounts of sodium hypophosphite [NaH2PO2] was added to deposit ternary CoPtP thin films. The film composition was adjusted by varying the several electrodeposition parameters including electrolyte composition, solution pH, and current density and correlated to their microstructure and magnetic property (i.e. coercivity and squareness). For the binary CoPt thin films, the maximum coercivities [in-plane coercivity (Hc,//) = ∼1,600 Oe, and perpendicular coercivity (Hc,⊥) = ∼2,500 Oe] were obtained from electrolytes containing 0.01 M H2PtCl6 + 0.04 M Co2P2O7 at current density (CD) of 7.5 mA cm−2. In the case of ternary CoPtP electrodeposits, the maximum coercivities (Hc,// = ∼2,600 Oe, and Hc,⊥ = ∼3,800 Oe) were achieved from baths containing 0.015 M H2PtCl6, 0.07 M Co2P2O7, 0.8 M NaH2PO2 at CD of 7.5 mA cm−2 and solution pH 9. It was suggested that microstructure and magnetic properties are affected not only by the type of substrate but also by chemical compositions and electrodeposition conditions.